Combined Heat and Mass Transfer by Mixed Convection Unsteady MHD Flow with Constant Heat and Mass Fluxes (Bangladesh Journal of Scientific and Industrial Research, 2008)
Combined heat and mass transfer by mixed convection unsteady MHD flow from a vertical porous plate with time dependent suction velocity and, constant heat and mass fluxes has been studied under the action of transverse applied magnetic field. The boundary layer equations have been transformed into dimensionless coupled nonlinear ordinary differential equations by similarity transformations. The solutions of the dimensionless coupled nonlinear ordinary differential equations are obtained by shooting iteration technique. The obtained numerical results are presented in the form of velocity, temperature and concentration distributions. Finally the effects of the pertinent parameters on the skin-friction coefficient are also examined. Key words : Combined heat and mass transfer, MHD flow, and Constant heat and Mass fluxes Â Â DOI = 10.3329/bjsir.v43i3.1146Bangladesh J. Sci. Ind. Res. 43(3), 309-320, 2008